Entre Thoth e Hermes Trismegisto : as cosmogonias egípcias na literatura hermética - Effgen, André Luís Silva (2023)
Hermetic Literature encompasses a collection of documents ranging from magical papyri with various incantations, treatises on astrology, instructions of an emerging alchemy, excerpts, and treatises of "philosophical-religious" nature. The main characteristic uniting this diverse documentation lies in the figure of Hermes Trismegistus (Ἑρμῆς Τρισμέγιστος). In almost all of these documents, the figure of Trismegistus is central, whether as a dramatis personae, a deity of worship, a pseudoepigraphic author of the documents, and often amalgamating all these roles. Hermetic Literature, for the most part of its trajectory as an object of academic study, has been examined and interpreted within a polarized debate. On one side, there are those who defend it as exclusively originating from Greek philosophy, while on the other, there are those who see beyond its birthplace and its mythical, hybrid, and syncretic founding character, finding much more from ancient Egyptian culture in its content. We intend to delve into the Egyptian legacy contained in these documents by analyzing their texts in comparison with earlier texts of mythicalreligious nature focused on the various cosmogonies originating from Egyptian civilization throughout its history. Our aim is to, through the theoretical framework provided by Aleida and Jan Assmann in their studies on cultural memory and the re-etymologization proposed by Peter Kingsley, identify possible elements of the body of traditions concerning the religious traditions of ancient Egypt, "under the Greek guise," from the Greco-Roman period.